Formation and inhibition of ethyl glucuronide and ethyl sulfate - Stachel, Nicole; Skopp, Gisela (Forensic science international, 2016)
Ethyl glucuronide (EtG) und ethyl sulfate (EtS) are widely accepted biomarkers in forensic and clinical settings. Even though, levels of EtG and EtS in blood and urine increase with increasing doses of alcohol, a high inter-individual variability in their production has been noticed. Therefore, we investigated the influence of dietary plant phenols on the formation of EtG and EtS and tentatively estimated the magnitude of in vivo inhibitory interactions from our in vitro results. To address these issues, formation of EtS and EtG was investigated using recombinant glucuronosyl- and sulfotransferases as well as human liver microsomes and liver cytosol. After respective kinetics had been established, inhibition experiments using quercetin, kaempferol and resveratrol were performed. These polyphenols are subject to extensive glucuronidation and/or sulfonation. EtG and EtS were determined by LC-MS/MS following solid phase extraction for EtG due to severe matrix effects and by direct injection for EtS. All enzymes investigated were involved in the conjugation of ethanol. Maximal EtG and EtS formation rates were observed with HLM and SULT1A1, respectively. All kinetics could best be described by Michaelis-Menten kinetics. Resveratrol was a competitive inhibitor of UGT1A1, UGT1A9 and HLM; quercetin and kaempferol were inhibitors of all transferases under investigation except UGT2B15. Findings for quercetin with regard to UGT2B7 and SULT2A1 and for kaempferol with regard to SULT1E1 and SULT2A1 suggested a mechanism based inhibition. Competitive inhibition of the glucuronidation and sulfonation of ethanol was estimated as weak to negligible and as moderate to weak, respectively. Beside the known polymorphisms of the transferases involved in EtG and EtS formation, prediction of the inhibitory potential indicates that polyphenols may contribute to the variable formation rate of EtG and EtS.